OPTIMASI JARINGAN INACORS UNTUK KEPERLUAN ANALISIS DEFORMASI DI KEPULAUAN SUMATRA MENGUNAKAN METODE SINGLE-OBJECTIVE OPTIMISATION MODELS OF PRECISION - Achmad Naufal, Irvan
Indonesia Continuously Operating Reference Station (InaCORS) is an active geodetic control network in Indonesia in the form of a permanent or continuous Global Positioning System (GPS) observation system. The main purpose of making InaCORS is to facilitate various forms of geodetic research and activities by providing an accurate, precise, and homogeneous reference system for all regions in Indonesia. Sumatra is one of the regions of Indonesia that is experiencing rapid economic growth, besides that the Sumatran region is also a disaster-prone area due to being between two active tectonic plates, namely the Eurasian plate and the Indo-Australian plate. This makes InaCORS an important part in facilitating development and as disaster mitigation. To support this, a geodetic control net, that is InaCORS, is needed with high accuracy, precise, and can detect deformation to facilitate the process of measuring and conducting geodetic research. For this reason, it is necessary to optimize the GNSS network which does not just increase accuracy, but also has sensitivity to detect displacement due to deformation. The purpose of this study is to optimize the InaCORS GPS network so that the network has an optimal shape, has a high level of precision at every point, and has a sensitivity level to detect a displacement of 5 mm. the method that will be used is the SOOM of Precision method. The data to be used is the coordinate of InaCORS Station in the Sumatra Island region, which will later be processed using Matlab. The Matlab software contains a program based on the SOOM of Precision method. The results obtained from this study are the optimal InaCORS Sumatra GPS that has a shift sensitivity level of 5 mm with a high level of precision.